2021
DOI: 10.1177/08912424211053599
|View full text |Cite
|
Sign up to set email alerts
|

Do Smart Cities Technologies Contribute to Local Economic Development?

Abstract: Governments around the world are exploring strategies that contribute to increased government performance and economic development that enable them to meet the service-tax expectations of their citizens. Within the framework of technology use in public management, this sudy examines the effects of smart cities technologies on the importance that chief administrative officers attach to local economic development. Drawing on the Digital Era Governance (DEG) model for theoretical context, this study uses logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…The primary factors contributing to hurdles include technical problems, insufficient infrastructure, and elevated implementation costs. These results are consistent with other research that has emphasized the challenges, in terms of both technology and finances, associated with the implementation of intelligent systems and digital infrastructure in diverse industries [100][101][102]. There is a need for an increased emphasis on developing advanced technologies appropriate for use in SCs and enhancing connection infrastructure inside urban areas.…”
Section: Discussionsupporting
confidence: 89%
“…The primary factors contributing to hurdles include technical problems, insufficient infrastructure, and elevated implementation costs. These results are consistent with other research that has emphasized the challenges, in terms of both technology and finances, associated with the implementation of intelligent systems and digital infrastructure in diverse industries [100][101][102]. There is a need for an increased emphasis on developing advanced technologies appropriate for use in SCs and enhancing connection infrastructure inside urban areas.…”
Section: Discussionsupporting
confidence: 89%
“…Participating stakeholders in governance processes, seeking more flexible ways to manage cooperation with partnerships, and integrating different political and administrative components are discussed in the smart city policies. Analyzing the relationship between the importance of local economic development and the application of smart city technologies using logistic regression, Abutabenjeh et al (2022, pp. 3–10) found that smart city technologies are important in local economic development where they are of low priority for local governments.…”
Section: Discussionmentioning
confidence: 99%
“…This not only facilitates the development of a new digital industry, but also accelerates the integration and reconstruction of the traditional manufacturing industry and digital technology, thus decreasing the dependence of industrial development on high-carbon energy sources, facilitating the industrial structural transition to digital and low-carbon models, decreasing energy consumption and carbon emission per unit output [43], and facilitating the urban transition to low-carbon energy sources. Finally, based on mass data sources and strong digital technologies, smart city construction can largely break spatial and temporal constraints on traditional knowledge and technological exchange [44] and develop new technologies, industries, and business states (e.g., energy storage technology, new energy sources, and intelligent traffic), which are closely related to energy production and consumption, decrease energy consumption, and can help realise low-carbon energy source development. To this end, we tested the following hypotheses: Hypothesis 1.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%